Drug Utilization Study of Diuretics in Children with Hydrocephalus - Indrawijaya, Yen Yen Ari; Sumarno, Sumarno; Suryaningtyas, Wihasto; Husna, Nuril Auliya (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v1i0.1497, 2021)
Hydrocephalus is a condition characterized by a dynamic imbalance between formation and absorption of cerebrospinal fluid that increases the size of intracranial space of the brain and, in some situations, an extension of the outer space of the brain with or without increased ventricular size. This study aimed to examine the use of diuretics and identify drug therapy problems in hospitalized children with hydrocephalus through the medical record. The study design is observational retrospective with time-limited sampling based on data in medical records at 2010-2013 periods, found 17 of 70 patients using diuretics therapy. There are three categories of diuretic which are used were mannitol (70.6%), acetazolamide (23.5%), and a combination of mannitol and acetazolamide (5.9%). Diuretics can be used for pre-op, post-op, and pre & post-op on all types of hydrocephalus. Still, the specific use of diuretics may be caused by variations in comorbid diagnoses, clinical data, and laboratory data for each patient. Adverse drug reactions are potentially dominant in DTP analysis, and these are 7 of 17 patients. Monitoring of serum electrolytes such as sodium and potassium is needed because it decreases are potential adverse drug reactions of diuretics.